2018
DOI: 10.1016/j.wasman.2017.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological conversion of crude glycerol derived from waste cooking oil to biodiesel

Abstract: In this study, crude, purified, and pure glycerol were used to cultivate Trichosporon oleaginosus for lipid production which was then used as feedstock of biodiesel production. The purified glycerol was obtained from crude glycerol by removing soap with addition of HPO which converted soap to free fatty acids and then separated from the solution. The results showed that purified glycerol provided similar performance as pure glycerol in lipid accumulation; however, crude glycerol as carbon source had negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…The difference is just that instead of glucose, purified crude glycerol is used for fermentation and micro-organism used for lipid production is T. oleaginosus. The fermentation has been considered from Chen et al (2018a) where 85% phosphoric acid was used for purifying crude glycerol through precipitation. The purified crude glycerol used during fermentation had (w/w) composition of 55% glycerol, 1.5% biodiesel, 4.2% ash, 18.5% methanol and 20.8% water.…”
Section: Microbial Lipid Production Using Crude Glycerol Media Followmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference is just that instead of glucose, purified crude glycerol is used for fermentation and micro-organism used for lipid production is T. oleaginosus. The fermentation has been considered from Chen et al (2018a) where 85% phosphoric acid was used for purifying crude glycerol through precipitation. The purified crude glycerol used during fermentation had (w/w) composition of 55% glycerol, 1.5% biodiesel, 4.2% ash, 18.5% methanol and 20.8% water.…”
Section: Microbial Lipid Production Using Crude Glycerol Media Followmentioning
confidence: 99%
“…Moreover, studies have been reported on the energy balance for biodiesel production from microbial oil using co-fermentation of crude glycerol and wastewater sludge (Chen et al, 2018a;Zhang et al, 2013;Zhang et al, 2016). However, those studies were done considering traditional downstream operations for biomass settling and lipid extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These impurities may inhibit cell growth and lipid production depending on the stain and concentration of the impurity [10]. Acidification is an effective method to remove soap, metals and salts from the crude glycerol [2,10,19]. However, purified glycerol obtained after acid treatment may contain several trace elements required for microbial growth, but they may not be present in sufficient concentration needed for lipid and citric acid production or they may not be consumed by microbe.…”
Section: Introductionmentioning
confidence: 99%
“…El interés por el desarrollo de aplicaciones para el glicerol crudo se debe a dos razones, una de ellas, el aumento de la oferta de este compuesto generado por la industrial del biodiésel, la otra se funda en los elevados costos del proceso de purificación que se trasladan a la materia prima . El exceso de glicerol puede afectar negativamente el mercado del biodiésel por eso se buscan alternativas de uso directo de este subproducto o tratamientos de purificación parcial (Chen et al, 2018) (Hejna, Kosmela, Formela, Piszczyk, & Haponiuk, 2016).…”
Section: Vi43 Influencia De La Relación Molar Entre Los Reactivosunclassified